Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858207
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Shifts to Suicidal Ideation from Mental Health Content in Social Media

Abstract: History of mental illness is a major factor behind suicide risk and ideation. However research efforts toward characterizing and forecasting this risk is limited due to the paucity of information regarding suicide ideation, exacerbated by the stigma of mental illness. This paper fills gaps in the literature by developing a statistical methodology to infer which individuals could undergo transitions from mental health discourse to suicidal ideation. We utilize semi-anonymous support communities on Reddit as uno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
436
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 577 publications
(447 citation statements)
references
References 63 publications
(72 reference statements)
7
436
2
2
Order By: Relevance
“…Additionally, online linguistic patterns match previous findings regarding language use of depressed individuals [16]. More recently, De Choudhury et al [10] have shown that linguistic features are important predictors in identifying individuals transitioning from mental discourse on social media to suicidal ideation. The authors showed a number of markers characterizing these shifts including social engagement, manifestation of hopelessness, anxiety and impulsiveness based on a small subset of Reddit posts.…”
Section: Literature Reviewsupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, online linguistic patterns match previous findings regarding language use of depressed individuals [16]. More recently, De Choudhury et al [10] have shown that linguistic features are important predictors in identifying individuals transitioning from mental discourse on social media to suicidal ideation. The authors showed a number of markers characterizing these shifts including social engagement, manifestation of hopelessness, anxiety and impulsiveness based on a small subset of Reddit posts.…”
Section: Literature Reviewsupporting
confidence: 80%
“…Social computing research has focused on this topic in recent years [6,9,10]. However, few initiatives have been concerned with the real time detection of suicidal ideation on Twitter.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring such venues can thus offer a window into behaviors which are otherwise difficult to study. Specifically, in the case of suicides, social media has been used to detect suicidality [20], and search engine logs were utilized to analyze suicides in general [21], [22] and the Werther Effect ("copycat suicides") in particular [21].…”
Section: Internet Data As a Source For Health Informationmentioning
confidence: 99%
“…Considering the frequent use of emotion language in status updates that relate to current experiences [13,14], for a large proportion of the population social media can provide unobtrusive access to time-sensitive and ecologically valid samples of expressed emotion [2,[41][42][43]. While observations of emotion variability and instability are yet to be applied to social media as a means of automatically screening for individuals at risk of depression, depression change has been demonstrated to be visible through changes in status update posting activity and content [2,4,10,44,45].…”
Section: Social Media and Emotion Dynamicsmentioning
confidence: 99%